Eksistensi Gerakan Sosial Semanggi Foundation Dalam Mewujudkan Aksi Sosial dan Kemanusiaan di Kota Tangerang - Arief, Arief Soetiawan; Yusuf Fadli; Agus Sutisna; Ahmad Chumaedy (Jurnal Noken: Ilmu-Ilmu Sosial, 2023)
The complexity of social problems faced by the community encourages the emergence of social movements that seek to provide assistance and empowerment programs that directly target the grassroots. The presence of the Semanggi Foundation movement in Tangerang City is engaged in providing support in the fields of humanity, education, culture and so on. This study aims to analyze various programs and activities carried out by the Semanggi Foundation and the extent to which they have an impact on the wider community. This study used a qualitative approach by using observation and interview techniques in taking research data. This research found that the Semanggi Foundation Social movement plays a positive role in people's lives. Its existence in the non-profit community helps people in the process of socializing and developing personal potential through a variety of dynamic activities. Social actions carried out by this movement cover various fields, such as humanitarian, educational, religious, and cultural arts. This research underscores the importance of the role of social movements in strengthening social solidarity and having a positive impact on society.